2023
DOI: 10.1126/sciadv.adg2838
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM visualization of DNA-PKcs structural intermediates in NHEJ

Abstract: DNA double-strand breaks (DSBs), one of the most cytotoxic forms of DNA damage, can be repaired by the tightly regulated nonhomologous end joining (NHEJ) machinery (Stinson and Loparo and Zhao et al. ). Core NHEJ factors form an initial long-range (LR) synaptic complex that transitions into a DNA-PKcs (DNA-dependent protein kinase, catalytic subunit)–free, short-range state to align the DSB ends (Chen et al. ). Using single-particle cryo–electron microscopy, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The DNA binding cradle interactions are required for both types of kinase activation. The reduction in 2056 phosphorylation with both the HHH and DEB mutants suggest that these DNA binding motifs are required for full kinase activation; moreover, the severe celllular phenotypes associated with these mutations are consistent with impaired formation of the DNA end protection complex which in cryo-EM structures is associated with full kinase activation 10 , 15 , 16 . Mutation of the DEB revealed that it is the failure of the DEB interaction with the DNA end that results in the partial and transient activation of DNA-PK; studies of DNA-PK activation by hairpin ends predicted this mechanism 10 .…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…The DNA binding cradle interactions are required for both types of kinase activation. The reduction in 2056 phosphorylation with both the HHH and DEB mutants suggest that these DNA binding motifs are required for full kinase activation; moreover, the severe celllular phenotypes associated with these mutations are consistent with impaired formation of the DNA end protection complex which in cryo-EM structures is associated with full kinase activation 10 , 15 , 16 . Mutation of the DEB revealed that it is the failure of the DEB interaction with the DNA end that results in the partial and transient activation of DNA-PK; studies of DNA-PK activation by hairpin ends predicted this mechanism 10 .…”
Section: Resultsmentioning
confidence: 77%
“…The enormous 4128 residue DNA-PKcs polypeptide is composed largely of well-ordered HEAT repeats with the relatively small lipid-like kinase domain positioned at the C-terminus of the polypeptide. Previously, a psi-pred analysis of DNA-PKcs predicted that ~200 residues that includes the functionally critical "ABCDE" autophosphorylation sites 23 was likely disordered; this is the same region that includes the DEB helix that can be visualized in both monomeric and dimeric structures [9][10][11][12][15][16][17][18]25 . Exactly what promotes the initial transition from a disordered region to the lone alpha helix DEB is not clear.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations